Kategori dan Emisi Sampah Laut (Macro-debris) Pada Muara Sungai Di Teluk Benoa, Bali - Br Purba, Catherina Brighida; Suteja, Yulianto; Perwira, Ima Yudha (Journal of Marine Research and Technology; Vol 8 No 1 (2025): FEBRUARI 2025DO - 10.24843/JMRT.2025.v08.i01.p08, 2025)
The worldwide issue of marine garbage negatively impacts the ecosystem, marine life, and people. Waste from the land that reaches the sea through rivers is one of the primary causes of marine trash. This investigation aim ed to determine the kind and emission of macro marine debris. The Badung, Loloan, Sama, and Punggawa Rivers are the four river estuaries of Benoa Bay, where the research was carried out in April 2024, during the first transitional season. A net was used to gather macro debris samples for 20 minutes, and the process was repeated thrice. Plastic was the most prevalent macro-debris type in all four river estuaries, with food wrappers, plastic bags, and plastic bottles being the most often discovered types. The four estuaries' daily macro-waste emissions were 13,752 pieces or 139.584 kg. According to the One Way ANOVA statistical test findings, there was a significant difference (p<0.05) in the quantity and weight of macro-waste from each research location. Since the settlement distance and density vary by location. The Punggawa River Estuary had the lowest emission of marine debris, at 2376 ± 259.59 items/day, or 20.80 ± 6.59 kg/day, while the Badung River Estuary had the highest, at 4824 ± 792 items/day, or 63.40 ± 23.57 kg/day. The study's ramifications highlight how urgent trash management is in the Benoa Bay River Estuary. In order to lessen the detrimental effects of trash on Bali's marine ecosystem, particularly in the seas of Benoa Bay, better management practices are required.